Research of Supersonic Free-Vortex Aerodynamic Window : 1st Report, Design Procedure of Free Vortex Nozzle and Operating Condition - OHIRA, Katsuhide; WADA, Tomohisa; SONODA, Keisuke; NANBA, Kazumi (Transactions of the Japan Society of Mechanical Engineers Series B, 1996)
In the development of continuous high-power gas laser systems, the supersonic free-vortex aerodynamic window is one of the key technologies for extracting a laser beam from the laser cavity. The present paper describes the design procedure of the two-dimensional supersonic free-vortex nozzle, and demonstrates the operating conditions of the window, taking into account the phase transition of the working fluid in the nozzle expansion process and the operating conditions of the supersonic diffuser. Generally, the high-power laser will be operated in the atmospheric environment without auxiliary equipment, i. e., a heater installed in the nozzle supply and/or a vacuum pump connected with the ventage of the supersonic diffuser. Therefore, the temperature of the working fluid at the nozzle supply is nearly 300 K, and the back pressure of the supersonic diffuser is inevitably atmospheric pressure. Hence, when using nitrogen gas as the working fluid in such an environment, the pressure ratio of the laser cavity to the atmosphere, which can be achieved with no phase transition, is about 20. In order to attain the higher pressure ratio of about 50, helium gas is required as the working fluid.